Efecto de las densidades de siembra en el rendimiento de yuca (Manihot esculentum Crantz) vr Valencia. - Moisés Blanco-Navarro; Víctor Aguilar-Bustamanete; Jose Rafael García-López; Chambar Baldioceda-Manzanares (Agronomía Mesoamericana, 2005)
En junio